Cuidados de enfermagem no pós-alta hospitalar de acidente vascular encefálico: uma revisão integrativa de literatura explorando estratégias de cuidados de enfermagem no pós-alta hospitalar de acidente vascular encefálico em pacientes - Lima, Livia Gabriele de Paula (Brasil, 2024)
Objective: To identify the main nursing care in the post-discharge period after a stroke. Method: This is an integrative literature review, the databases used in the search process were: PubMed and BVS. Inclusion criteria: Full-text, freely available articles in Portuguese or English published in the last 10 years (2013 to 2023). Results: The search of the databases revealed 552 articles in PubMed and 1256 in the VHL, resulting in 1808 publications which, after applying the inclusion and exclusion criteria and the PRISMA strategy, resulted in the selection of 9 publications. Conclusion: Post-stroke nursing care focuses on prevention and health promotion, with an emphasis on lifestyle changes and physical exercise. Nursing plays a crucial role in the rehabilitation team, offering great assistance. However, the low level of evidence in the studies reviewed points to the need for more solid research.